New Mechanistic Insight into Stepwise Metal‐Center Exchange in a Metal–Organic Framework Based on Asymmetric Zn4 Clusters. Issue 10 (7th February 2014) - Meng, Wei; Li , Huijun; Xu , Zhouqing; Du, Shanshan; Li, Yunxia; Zhu, Yanyan; Han , Yi; Hou, Hongwei; Fan, Yaoting; Tang, Mingsheng
Abstract Herein, a mechanism of stepwise metal‐center exchange for a specific metal–organic framework, namely, [Zn4(dcpp)2(DMF)3(H2O)2]n (H4dcpp=4, 5‐bis(4′‐carboxylphenyl)phthalic acid), is disclosed for the first time. The coordination stabilities between the central metal atoms and the ligands as well as the coordination geometry are considered to be dominant factors in this stepwise exchange mechanism. A new magnetic analytical method and a theoretical model confirmed that the exchange mechanism is reasonable. When the metathesis reaction occurs between CuII ions and framework ZnII ions, the magnetic exchange interaction of each pair of CuII centers gradually strengthens with increasing amount of framework CuII ions. By analyzing the changes of coupling constants in the Cu‐exchanged products, it was deduced that Zn4 and Zn3 are initially replaced, and then Zn1 and Zn2 are replaced later. The theoretical calculation further verified that Zn4 is replaced first, Zn3 next, then Zn1 and Zn2 last, and the coordination stability dominates the Cu/Zn exchange process. For the Ni/Zn and Co/Zn exchange processes, besides the coordination stability, the preferred coordination geometry was also considered in the stepwise‐exchange behavior. As NiII and CoII ions especially favor octahedral coordination geometry in oxygen‐ligand fields, NiII ions and CoII ions could only selectively exchange with the octahedral ZnII ions, as was also confirmed by the experimental results. The stepwise metal‐exchange process occurs in a single crystal‐to‐single crystal fashion.